Perkembangan Bioinformatics dalam Ruang Lingkup Ilmu Komputer - Irma Yunita; Kristian Tjandradiredja; Seng Hansun (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2016)
Bioinformatics is a research topic which is very attractive in this era. Bioinformatics combines biology and computer science. It means that biology problem can be solved by using methods and techniques in solving problems in computer science. There are some terms of bioinformatics such as DNA, RNA, and protein. In addition, there are several methods described in this paper, which can be used in solving the problem bioinformatics following with the tools and software which are available and free in internet. Keywords—bioinformatics, tools of bioinformatics, methods of bioinformatics